Doing and undoing gender by women with intellectual disabilities - Zierkiewicz, Edyta; Cytowska, Beata (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Edyta Zierkiewicz, Beata Cytowska, Doing and undoing gender by women with intellectual disabilities. Interdisciplinary Contexts of Special Pedagogy, no. 26, Poznań 2019. Pp. 271–293. Adam Mickiewicz University Press. ISSN 2300-391X. e-ISSN 2658-283X. DOI: https://doi.org/10.14746/ikps.2019.26.13 The aim of this article is to present socio-cultural processes of doing gender categories in women with intellectual disabilities and to identify barriers and limitations which they face on the way of „becoming women”. The study and its analysis are based on the critical approach. The method of data collection was a participant observation conducted during three proprietary workshops on femininity organized for 17 women with moderate to severe intellectual disabilities (5–6 people in a group), attending an occupational therapy workshop. The aim of our workshops was the empowerment of one’s own femininity and strengthening of processes of doing gender by the participants. The analysis of collected material revealed that the process of shaping gender identities of women with intellectual disability is a subject of social control of the local community. Participants of the workshops are well aware that they are adult women and they strive for the realization of cultural patterns of femininity. In their case, however, these patterns are socially regulated and the women themselves internalize certain limitations imposed by the society during the socialization process. They instinctively “know” what they are allowed to do, and what they cannot gain as women with intellectual disabilities.